Explanation:
We will use the equations of constant acceleration to find out [tex]a_{x}[/tex] and time t.
As we know that the initial speed is zero. So
(a)
[tex]v_{0x} = 0[/tex]
[tex]x - x_{o} = 1.25[/tex]×[tex]10^{-2}[/tex]m
[tex]v_{x} = 3.3[/tex]×[tex]10^{6}[/tex]m/s
[tex]v^{2} _{x} = v^{2} _{x_{o} } + 2a_{x} (x - x_{o} )[/tex]
[tex]a_{x} = \frac{v^{2} _{x} - v^{2} _{ox} }{2(x - x_{o}) }[/tex]
= [tex]\frac{(3.3 * 10^{6})^{2} - 0 }{2(1.25 * 10^{-2}) }[/tex]
= 4.356×[tex]10^{14}[/tex] m/s²
(b)
[tex]v_{x} = v_{ox} + a_{x}t[/tex]
[tex]t = v_{x} - vo_{x}/a_{x}[/tex]
[tex]t = \frac{3.00 * 10^{6} }{4.356*10^{14} }[/tex] = 6.8870×[tex]10^{-9}[/tex]s
(c)
Σ[tex]F_{x} = ma_{x}[/tex]
= (9.11×[tex]10^{-31}[/tex])(4.356×[tex]10^{14}[/tex]m/s²)
= 3.968×[tex]10^{-16}[/tex] N